(untitled) (Bangladesh Journal of Animal Science, 2017)
An experiment was conducted to investigate the effect of supplementing of exogenous phytase enzyme on productivity of commercial broilers. Four strains of commercial broiler such as Fast feather, Arbor acres, Cobb-500 and Hubbard classic each having 78 numbers were reared for a period of 5 weeks. A total number of 312 day old broiler chicks were distributed into two dietary treatments i.e. basal diet (Control-T0) and basal diet supplemented with phytase enzyme 1g/kg feed (supplemented-T1). The results indicated that broilers fed on diets supplemented with phytase have gained more body weight when compared with control group (P<0.05). The first and second highest body weights were recorded for the strains Cobb-500 and First feather broilers, respectively, which feed on diet containing phytase. Feed consumption varied significantly between the broilers on different dietary regimes. Significant differences (P<0.01) were found in feed conversion ratios among the birds fed on diet with phytase enzyme. The lowest feed conversion ratio was in Cobb-500 fed on phytase diet where as the highest was in Fast Feather provided with only basal diet during the 5th week of age. Average feed conversion ratios were 1.73 and 1.86 for the supplemented and control group respectively. Use of phytase as feed additive in the diet resulted in high profitability/ broiler. Net profit per live broiler was the also higher in treatment group compared with control groups of birds. The highest net profit per live broiler was observed in Arbor Across strains fed on phytase diet. The result of the present study suggests that the addition of dietary phytase enzyme in the diet of broiler may increase the production performance and reduce the cost of production. Bang. J. Anim. Sci. 2016. 45 (3): 31-39